Penerapan Asas Going Concern Sebagai Upaya Perlindungan Hukum Terhadap Debitor Dalam Proses Kepailitan Di Indonesia: The Application of the Going Concern Principle as a Means of Legal Protection for Debtors in the Indonesian Bankruptcy Process - Ulkhaq, M Rifqy Dhiya; Gultom, Elisatris; Sudaryat, Sudaryat (PUSDATIN Institut Agama Islam Sultan Muhammad Syafiuddin Sambas, 2025)
The application of the going concern principle within Indonesia's bankruptcy law system is a crucial legal protection mechanism for debtors facing financial difficulties. This study aims to analyze the implementation of the going concern principle as a form of legal protection for debtors in the bankruptcy process in Indonesia. This research employs a normative juridical method with a statutory approach and case study analysis. The results indicate that the going concern principle is implemented through the Suspension of Debt Payment Obligations (PKPU) mechanism, as regulated in Law No. 37 of 2004 concerning Bankruptcy and PKPU. The findings show that although the going concern principle provides significant protection for debtors by offering an alternative to liquidation, its implementation faces several challenges, including creditor resistance, resource limitations, and regulatory gaps. The study concludes that the going concern principle is effective in balancing the interests of debtors and creditors, though improvements in the regulatory framework and implementation capacity are needed to enhance its effectiveness in protecting debtors' rights while maintaining creditor confidence.